Identification of phenotypic abnormalities and effector function impairment in natural killer cells of patients with ataxia-telangiectasia - Aurora Nenci; Maria Giovanna Desimio; Elisa Profeti; Beatrice Rivalta; Luca Pollini; Vincenzo Leuzzi; Mattia Moratti; Francesca Conti; Davide Montin; Gessica Vasco; Caterina Cancrini; Andrea Finocchi; et al. (Journal of Translational Medicine, 2026)
Abstract Background Ataxia-telangiectasia (A-T) is a rare inherited disorder resulting from mutations in the ATM gene and characterized by progressive neurodegeneration, immunological abnormalities, and increased infection and cancer susceptibility. There is no cure for A-T, and life expectancy is drastically reduced because of pulmonary disease and cancer. Humoral or T/B-cell deficiency was associated with reduced survival in A-T patients, although the findings remain controversial. Conversely, A-T patients display normal numbers of NK cells, crucial components of the antitumor and antiviral innate immunity. The goal of the present study was to investigate the function of NK cells in A-T. Methods Peripheral blood NK cells of 31 A-T patients were analyzed via flow cytometry to assess their distribution across subpopulations and expression of maturation markers, receptors and effector molecules. Additionally, we assessed the capacity of NK cells to kill K562 cells and to produce IFN-γ in response to IL-12/IL-15/IL-18 stimulation. The plasma levels of soluble ligands for the NKG2D receptor (sNKG2DLs) and cytokines were measured via ELISA. Results Compared with control NK cells, A-T patient NK cells presented higher frequencies of the CD56 bright and CD56 dim CD16 − subsets and contraction of the highly cytotoxic CD56 dim subset that, however, showed a normal maturation pattern. The expression of the main activating/inhibitory receptors was conserved on A-T NK cells, except for the up- and downregulation of PD-1 and NKG2D, respectively. NKG2D downregulation correlated with accumulation of the sNKG2DLs sMICA and sULBP2 in patient plasma. Importantly, A-T NK cells were inefficient at producing IFN-γ upon stimulation and strongly impaired at killing tumor targets, dysfunctions that were reproduced by inhibiting ATM in PBMCs of healthy individuals. Finally, in A-T plasma, we detected elevated levels of IL-6, which correlated with NK-cell phenotypic alterations and reduced IFN-γ response, and increased levels of TGF-β, which correlated with impaired NK-cell cytotoxicity. Conclusion The present study fills a gap in the field of A-T immunity, revealing exhaustion-associated features and functional impairment of NK cells correlated with increased plasma concentrations of sNKG2DLs and the immunosuppressive cytokines IL-6 and TGF-β. These findings indicate that NK defects can contribute to cancer and infection susceptibility and provide hints for improving current therapies for A-T.